Pengaruh Pemberian Kredit Terhadap Return on Assets Pada Perbankan Bumn Tahun 2016 – 2020 - Nijar Kurnia Romdoni; Ernawati; Muis Wirasujatma (LPPM POLITEKNIK LP3I BANDUNG, 2022)
This study aims to determine how big the influence of lending on return on assets in state-owned banking for the 2016 - 2020 period. The variables in this study are lending (X) and return on assets (Y). The population includes the overall financial statements of state-owned banking and the sample of this study is the financial statements of state-owned banks for the last five years from 2016 - 2020. The data collection techniques used are documentation and literature review. The data analysis technique used in this research is Simple Regression Analysis, f-test, t-test and Coefficient of Determination Test. The results of the study indicate that the provision of credit has a significant positive effect on Return on Assets.